READING APP REVIEWS AND TRYING APPS IN PREDICTING THE USE OF COMMUNICATION APPS: AN EXPERIMENTAL STUDY OF THE RELATIONSHIP AMONG BEHAVIOR, ATTITUDE AND INTENTION TO USE - Niken Febrina Ernungtyas; Irwansyah Irwansyah (Fakultas Seni Rupa dan Desain ITB, 2019)
This study examines the relationship among reading app reviews, trying apps, attitude and intention to use the communication apps. Attitude towards apps and intention to use apps change as a result of app reviews and trials. An experiment was conducted in a rural area testing twelve communication apps with 80 participants who were not communication app users. The relationship of the variables was analyzed using statistical regression. This study found that treatments do not affect attitude or intention to use. Meanwhile, significantly, attitude can moderately predict intention to use. Intention to use communication apps was not related to app reviews and trials but related to participants' attitudes. The findings suggest that this experiment did not use an appropriate method to confirm theoretical modelling of the TAM, TRA and TPB. Future research involving other variables (perceived usefulness, perceived ease of use etc.) is needed to reveal comprehensive modelling to predict the intention to use. Penelitian ini mengkaji hubungan membaca review aplikasi, mencoba aplikasi, sikap, dan niat menggunakan aplikasi komunikasi. Sikap terhadap aplikasi dan niat menggunakan aplikasi berubah sebagai hasil dari review dan mencoba aplikasi. Eksperimen dilakukan di wilayah perdesaan untuk menguji dua belas aplikasi komunikasi dengan 80 partisipan yang bukan pengguna aplikasi komunikasi. Hubungan antarvariabel dianalisis menggunakan regresi statistik. Dari penelitian ini ditemukan perlakuan pada eksperimen tidak memengaruhi sikap maupun niat menggunakan aplikasi. Namun, sikap dapat memprediksi niat menggunakan aplikasi pada level moderat. Niat menggunakan aplikasi komunikasi tidak terhubung dengan review dan mencoba aplikasi tetapi terhubung dengan sikap partisipan. Hasil temuan menunjukkan eksperimen ini tidak cocok untuk mengonfrmasi model teori TAM, TRA, dan TPB. Penelitian selanjutnya yang melibatkan variabel lain (perceived usefulness, perceived ease of use, dsb) diperlukan untuk membuat model komprehensif yang dapat memprediksi niat menggunakan aplikasi.